The generalizability of Older Adult Self-Report (OASR) syndromes of psychopathology across 20 societies - Masha, Ivanova; Portillo Reyes, Veronica; Achenbach, Thomas; Rescola, Leslie; Turner, Lori; Dumas, Julie; Almeida, Vera; Anafarta-Sendag, Meltem; Bie, Leva; Bolmsma, Dorret; Caldas, Carlos; Capps, John; et al. (2020)
OBJECTIVES: As the world population ages, psychiatrists will increasingly need instruments for measuring constructs of psychopathology that are generalizable to diverse elders. The study tested whether syndromes of co-occurring problems derived from self-ratings of psychopathology by US elders would fit self-ratings by elders in 19 other societies.